The Effect of Cash Ratio and Loan to Asset Ratio on Return on Asset at PT. Bank Mandiri Tbk - Puput Jahsinia Putri; Aliah Pratiwi; Nurhayati (Journal AGENCY, 2026)
This study examines the effect of liquidity and asset allocation on bank profitability by analyzing the influence of Cash Ratio (CR) and Loan to Asset Ratio (LAR) on Return on Assets (ROA) at PT Bank Mandiri Tbk. As one of Indonesia’s largest state-owned banks, maintaining optimal liquidity and productive asset utilization is essential to sustaining financial performance and public trust. This research aims to determine the partial and simultaneous effects of CR and LAR on ROA. A quantitative associative approach was employed using secondary data derived from the bank’s annual financial statements over the 2014–2023 period. The sample consisted of 10 years of observations selected through purposive sampling. Data were analyzed using multiple linear regression, supported by classical assumption tests, t-tests, F-tests, and coefficient of determination analysis with a 5% significance level. The results indicate that Cash Ratio has a positive and significant effect on ROA, suggesting that improved liquidity strengthens financial stability and enhances profitability. Similarly, Loan to Asset Ratio demonstrates a positive and significant effect on ROA, indicating that a higher proportion of productive earning assets contributes to increased income generation. Simultaneously, CR and LAR significantly influence ROA. These findings highlight the importance of balancing liquidity management and loan allocation strategies to optimize bank profitability and ensure sustainable financial performance.